SIFAT FISIS DAN SIFAT MEKANIS KAYU KENANGA (Cananga ordorata) DAN SENGON (Paraserienthes falcataria) TERMODIFIKASI PANAS - Lestari, Dini; Ningsih, Rima Vera; Shabrina, Hasyyati; Fahrussiam, Fauzan (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
Kenanga and sengon wood are known for their inferior properties, necessitating effort to enhance their quality. In Wood Industry, thermal modification was used to enhance wood properties especially dimensional stability. The objective of this research was to evaluated the effect of wood species and thermal modification on physical and mechanical properties of wood. The wood modified by steam treatment at temperature of 1260C at pressure of 0.14 MPa for 1 hour. The physical properties tested included density, moisture content, volumetric swelling, and anti-swelling efficiency. The mechanical properties tested were the modulus of elasticity and modulus of rupture. The mechanical properties of the wood were tested according to ASTM D 143-05 (1996), and all parameters were compared between the thermal-modified wood and the control. The results showed that the density and moisture content parameters were only influenced by wood species while thermal modification and interaction of wood species and thermal modification did not affect density and moisture parameters. Furthermore, heat modification significantly improved the dimensional stability of the wood, as evidenced by a decrease in volumetric swelling and anti-swelling efficiency value higher than 40%. Additionally, heat modification slightly enhanced the mechanical properties of kenanga and sengon wood as seen from the increased values of modulus of elasticity and modulus of rupture values.